Improving the Learning Outcomes of Second-Grade Elementary School Students in Weight Measurement Through the Think-Pair-Share Model Assisted by Polypad Media - Juwita Tumeida; Lasim Muzammil; Qomariyah (Journal of Practice Learning and Educational Development, 2026)
This study aims to improve the learning outcomes of second grade elementary school students on weight measurement material through the implementation of the Think Pair Share (TPS) learning model assisted by Polypad media. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 28 students of class II at SD Negeri Tanjungrejo 5. Data were collected through observation and tests (pre-test and post-test), then analyzed using qualitative and quantitative descriptive techniques. The results showed that student learning outcomes improved significantly. The classical completeness increased from 10.7% in the pre-cycle to 60.71% in cycle I, and reached 85.71% in cycle II, exceeding the minimum completeness criteria (KKM) of 70. The findings indicate that the TPS model assisted by Polypad media effectively enhances student engagement, conceptual understanding, and learning outcomes in weight measurement material.